The Influence Of Work Discipline And Motivation On Employee Performance At PT Expert Jaya Mandiri, Tangerang Selatan City - Abid, Muhamad; Rukmana, Nila (IJOSMAS, 2022)
This study aims to determine the effect of discipline and work motivation on the performance of employees of PT. Expert Jaya Mandiri, South Tangerang City. This study uses quantitative methods with the sample used in this study as many as 55 respondents. The sampling technique used the Saturated sample. Data collection using SPSS 25 program. Data analysis using validity test, reliability test, classical assumption test, regression analysis, coefficient of determination analysis in hypothesis testing. The results of this study are a discussion of the effect of discipline and work motivation on employee performance, as follows: Discipline has a significant effect on employee performance with the regression equation Y = 12,501 + 0.230 X1, the correlation value is 0.230, meaning that both variables have a strong relationship with the coefficient of determination by 62%. Hypothesis test obtained t count > t table or (2,209 > 2,007). Thus Ho is rejected and H1 is accepted, meaning that there is a significant influence between discipline on employee performance. Motivation has a significant effect on employee performance with the regression equation Y =12,501 + 0.448 X2, the correlation value is 0.448, meaning that the two variables have a strong relationship level with a coefficient of determination of 62%. Hypothesis test obtained t count > t table or (4,953 > 2,007). Thus Ho is rejected and H2 is accepted, meaning that there is a significant influence between work motivation on employee performance. Discipline and work motivation have a significant effect on employee performance with the regression equation Y = 12,501 + 0,230 X1+ 0,448 X2. The correlation value of 0.796 means that the independent variable and the dependent variable have a strong relationship with a coefficient of determination of 62% while the remaining 38% is contributed by other factors. Hypothesis test obtained value Fcount > Ftable or (44.983 > 4.03 ). Thus Ho is rejected and H3 is accepted. This means that there is a simultaneous significant influence between Discipline and Work Motivation on Employee Performance at PT. Expert Jaya Mandiri, South Tangerang City.